7-Methoxy-1-Tetralone Induces Apoptosis, Suppresses Cell Proliferation and Migration in Hepatocellular Carcinoma via Regulating c-Met, p-AKT, NF-κB, MMP2, and MMP9 Expression - Wen, Ying; Cai, Xiaoyan; Chen, Shaolian; Fu, Wei; Chai, Dong; Zhang, Huainian; Zhang, Yongli (Frontiers in Oncology, 2020)
This study aimed to determine the anti-proliferative and anti-migratory effects of 7-methoxy-1 -tetralone (MT) in hepatocellular carcinoma (HCC) cells. MTT assay assessed HCC cell viability; cell apoptosis of HCC cells was determined by flow cytometry; wound healing assay evaluated HCC cell migratory ability; protein expression levels were assessed using western blot assay; the in vivo antitumor effects of MT were tested in BALB/c nude mice and the pathological changes within the tumor tissues were evaluated by immunohistochemistry. MT treatment significantly suppressed the cell proliferative and migratory potentials of HepG2 cells, and induced HepG2 cell apoptosis. The western blot assay showed that MT treatment caused a suppression on c-Met, phosphorylated AKT (p-AKT), NF-κB, matrix metallopeptidase 2 (MMP2)/MMP9 protein levels in HepG2 cells. Further in vivo animal studies deciphered that MT treatment suppressed tumor growth of HepG2 cells in the nude mice, but had no effect on the body weight and the organ index of liver and spleen. Further immunohistochemistry analysis of the dissected tumor tissues showed that MT treatment significantly suppressed the protein expression levels of NF-κB, MMP9, MMP2 and p-AKT. In summary, the present study demonstrated the anti-tumor effects of MT on the HCC, and MT suppressed HCC progression possibly via regulating proliferation- and migration-related mediators including c-Met, p-AKT, NF-κB, MMP2 and MMP9 in HepG2 cells.